2013
DOI: 10.1007/s11239-013-0953-5
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer levels predict ischemic and hemorrhagic outcomes after acute myocardial infarction: a HORIZONS-AMI biomarker substudy

Abstract: D-dimer is a product of cross linked fibrin degradation and is a measure of the amount of fibrin turnover. As such, D-dimer might be of utility in the prediction of both thrombotic and hemorrhagic events. Therefore, the aim of the present study was to evaluate whether elevated D-dimer levels on admission and at discharge could predict subsequent ischemic and hemorrhagic events in patients with acute myocardial infarction (AMI). D-dimer was measured on admission and at discharge in 461 out of a total of 3,602 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
3
43
0
2
Order By: Relevance
“…Only one report showed that higher levels of D-dimer can predict systemic bleeding (including intracranial hemorrhage) in acute myocardial infarction [19] . The mechanism of the independent association between higher D-dimer and symptomatic ICH in our study may be similar to the aforementioned.…”
Section: Discussionmentioning
confidence: 99%
“…Only one report showed that higher levels of D-dimer can predict systemic bleeding (including intracranial hemorrhage) in acute myocardial infarction [19] . The mechanism of the independent association between higher D-dimer and symptomatic ICH in our study may be similar to the aforementioned.…”
Section: Discussionmentioning
confidence: 99%
“…Ddimer, a product of cross-linked fibrin degradation, is a measure of the amount of fibrin turnover and might be of utility in the prediction of both thrombotic and hemorrhagic adverse events (12). Currently, emerging evidence endorses a 'predictive' role for increased D-dimer levels, since its measurement provides prognostic data for a variety of conditions, including venous thromboembolism, cardiovascular diseases, infectious diseases, and cancer (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In such a condition, infectious disease like IE leads to increased morbidity and mortality(37). Circulating concentration of D-dimer is an activation marker of fibrinolysis and, therefore, of coagulation and reflects the extent of fibrin turnover(12).Recently, increased D-dimer level emerged as a significant predictor of morbidity and mortality in various clinical conditions including venous thromboembolism, cardiovascular diseases like myocardial infarction and aortic dissection, infectious diseases like sepsis, and cancer(13)(14)(15)(16)(17)(18)38). In a study including 42 patients, Bakal et al (39) showed that plasma Ddimer levels have been increased in patients with IE who suffered from clinically significant systemic embolism and D-dimer >425 ng/dl demonstrated a sensitivity of 77% and specificity of 62% for the prediction of clinical embolism.…”
mentioning
confidence: 99%
“…In recent years, DD had been reported to be a marker for the early diagnosis of ACS presenting with chest pain [8] and acute myocardial infarction (AMI) [9] . Furthermore, DD had been found to be associated with short-, mid-and long-term poor outcomes in patient with AMI [10][11][12] . In addition, as a marker of increased coagulability and fibrinolysis, DD also had been documented to be associated with renal insufficiency, which indicated that DD concentration increased significantly with increasing creatinine levels [13] or decreasing estimated glomerular filtration rate(GFR) [14] .…”
Section: Introductionmentioning
confidence: 99%